Sn-doped defect-state mesoporous TiO2 catalyst as well as preparation method and application thereof

By doping the defective mesoporous TiO2 catalyst in the Sn-doped defective state, the problem of difficult to obtain high molecular weight and light color products in the direct esterification method of glycolic acid is solved, and the efficient catalytic synthesis of polyglycolic acid is achieved, which reduces energy consumption and tin residues and improves the Product quality.

CN119119449APending Publication Date: 2024-12-13CHINA SHENHUA COAL TO LIQUID & CHEM CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411269509.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In the prior art, it is difficult to obtain high molecular weight and light color polyglycolic acid through direct esterification of glycolic acid, which has low catalytic efficiency and the residue of tin catalysts lead to accelerated degradation, which limits the application of polyglycolic acid.

Method used

The Sn-doped defective mesoporous TiO2 catalyst is prepared by alcoholylation and hydrothermal reaction, and is used for direct esterification of glycolic acid to optimize the specific surface area and particle size of the catalyst, reduce the use of metal Sn, and improve catalytic activity.

Benefits of technology

It is achieved to obtain high molecular weight and light color polyglycolic acid under a relatively small amount of catalyst, which reduces reaction time and energy consumption, inhibits product yellowing, and improves the reaction efficiency and product quality of direct esterification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119449A_ABST
    Figure CN119119449A_ABST
Patent Text Reader

Abstract

The invention provides a Sn-doped defect-state mesoporous TiO2 catalyst as well as a preparation method and application thereof, the catalyst is used for preparing polyglycolic acid by a glycolic acid direct esterification method, and high-quality polyglycolic acid with high molecular weight and light color can be obtained. The preparation method comprises the following steps: (1) carrying out alcoholysis on a titanium compound in polyhydric alcohol according to a molar ratio of the titanium compound to the polyhydric alcohol of 0.005-0.5, and carrying out alcoholysis to obtain TiO2 nanoparticles; then adding alkali liquor and alcohol with reduction potential, carrying out solvothermal reaction at 120-220 DEG C, washing and separating the obtained product, and then drying to obtain defect-state mesoporous TiO2; and (2) dispersing the defect-state mesoporous TiO2 obtained in the step (1) in a tin compound aqueous solution, carrying out a hydrothermal reaction at 100-200 DEG C, and washing, separating and drying the obtained product to obtain the catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polyglycolic acid (PGA) preparation, and in particular to a Sn-doped defective mesoporous TiO2 particularly suitable for preparing polyglycolic acid (PGA) by direct esterification. 2 Catalyst, preparation method and application thereof. Background Art

[0002] Polyglycolic acid (PGA) is an emerging highly crystalline semi-crystalline bio-friendly degradable polyester material with both biodegradability and biocompatibility. It plays an important role in biomedical fields such as surgical clinical medical sutures and tissue scaffolds. Its final degradation products in the body are water and carbon dioxide. Compared with polylactic acid (PLA), it has a faster degradation rate and better biocompatibility. When used in the body, it is beneficial to cell proliferation and cell adhesion. It has been widely used in medicine and is a biomedical material with good development prospects. Polyglycolic acid (PGA) has the advantages of excellent biocompatibility, mechanical properties, high barrier properties, high load deformation temperature, etc. It is a rare degradable engineering polymer material. Its biodegradability is similar to that of natural cellulose. At the same time, it meets the requirements of industrial composting, household composting and seawater degradation. It has been certified as a safe biodegradable plastic material in the United States, the European Union, Japan and other countries. It is widely used in high-end biomedicine, food packaging, shale and oil extraction and agricultural production, and has a broad market space.

[0003] At present, the synthesis methods of polyglycolic acid with industrial value include direct polycondensation and glycolide ring-opening polymerization. At present, the synthesis of PGA at home and abroad is mainly based on glycolide ring-opening polymerization, which has high requirements for the purity of glycolide and high product cost. It is mainly produced on a large scale in Japan and the United States.

[0004] In recent years, with the development of coal chemical technology and the breakthrough of key technology for preparing glycolic acid (methyl ester) from dimethyl oxalate at low cost, my country's PGA industry has brought important turning points and hope. The rapid growth of domestic glycolic acid monomer production scale and the reduction of costs make direct polymerization more likely to become the preferred solution for large-scale production of PGA in the future.

[0005] In terms of research on the direct synthesis of PGA, according to current patent and literature search analysis, there are 72 results (Scifinder search results) for the direct melt polymerization method for synthesizing PGA, but there is little reference information, only 11 references, and there is no report on the synthesis of high molecular weight (Mn>50000Da) light-colored PGA. In summary, the high technical difficulty of the direct esterification polymerization route has brought challenges and opportunities to the development of the entire industry.

[0006] The method of synthesizing PGA by direct polycondensation of glycolic acid is shorter and less expensive than the ring-opening polymerization of glycolide, and is more suitable for the production of bulk products. However, it is generally reported that this method is difficult to synthesize products with higher molecular weight and lighter color, which greatly limits the application of PGA. The direct esterification method often uses tin catalysts, such as stannous chloride dihydrate, stannous octoate, stannous chloride, tin oxide, etc. The low catalytic efficiency leads to a long reaction time, resulting in poor color of the polyglycolic acid product. If an excess of tin catalyst is used, it will usually remain in the polymer system and cannot be removed. Excessive tin catalyst residues will accelerate the degradation of polyglycolic acid. Summary of the invention

[0007] In view of the technical difficulty of preparing polyglycolic acid by direct esterification of glycolic acid in the prior art, it is difficult to obtain polyglycolic acid with high molecular weight and light color. The present invention provides a Sn-doped defective mesoporous TiO 2 The catalyst and its preparation method and application are disclosed. The catalyst of the invention is used for preparing polyglycolic acid by direct esterification of glycolic acid, so as to obtain high-quality polyglycolic acid with high molecular weight and light color.

[0008] To achieve the purpose, the present invention provides the following technical solutions:

[0009] The present invention provides a Sn-doped defective mesoporous TiO 2 The method for preparing the catalyst comprises the following steps:

[0010] (1) alcoholyzing a titanium compound in a polyol, wherein the molar ratio of the titanium compound to the polyol is 0.005 to 0.5, and obtaining TiO 2 Then, an alkali solution and an alcohol with a reducing potential are added to carry out a solvent thermal reaction at 120 to 220°C, and the obtained product is washed, separated, and then dried to obtain defective mesoporous TiO 2 ;

[0011] (2) The defective mesoporous TiO obtained in step (1) 2 The catalyst is obtained by dispersing the catalyst in a tin compound aqueous solution and performing a hydrothermal reaction at 100-200°C. The obtained product is washed, separated and then dried.

[0012] In some embodiments, in step (1), the titanium compound is selected from one or more of tetrabutyl titanate, isopropyl titanate, cesium titanate, potassium titanate, titanyl sulfate, titanium tetrachloride, and titanium trichloride, preferably tetrabutyl titanate and / or titanium tetrachloride, more preferably titanium tetrachloride;

[0013] And / or, in step (1), the polyol is selected from one or more of propylene glycol, glycerol, ethylene glycol, butylene glycol, and pentanediol, preferably propylene glycol;

[0014] And / or, in step (2), the tin compound is selected from one or more of tin dioxide, tin dichloride, tin tetrachloride, stannous oxalate, tin sulfide, and tin nitrate, preferably tin dichloride and / or tin nitrate, more preferably tin dichloride.

[0015] Preferably, the molar ratio of the titanium compound to the polyol is 0.007-0.2.

[0016] In some embodiments, in step (1), the alkali solution is an aqueous solution of an alkaline compound;

[0017] In step (1), the molar ratio of the alkaline compound in the alkali solution to the alcohol having a reducing potential is 0.05 to 0.2; and the molar ratio of the alkaline compound to the titanium compound is 10 to 0.5.

[0018] In some embodiments, the alkaline compound in the alkali solution is selected from one or more of sodium hydroxide, potassium hydroxide, magnesium hydroxide, aluminum hydroxide, potassium oxide, and potassium carbonate, preferably potassium hydroxide;

[0019] And / or, the alcohol having a reducing potential is selected from one or more of n-butanol, 1,4-butanediol, 1,5-pentanediol, ethylene glycol, propylene glycol, and ethanol, preferably n-butanol.

[0020] In some embodiments, the molar ratio of the tin compound used in step (2) to the titanium compound used in step (1) is 0.05 to 0.3;

[0021] Preferably, the concentration of the tin compound aqueous solution is 0.01-0.5 mol / L.

[0022] In some embodiments, in step (1), the alcoholysis temperature is 25 to 200° C., and the alcoholysis time is 0.5 to 12 h;

[0023] And / or, in step (1), the solvent thermal reaction time is 2 to 12 hours;

[0024] And / or, in step (2), the hydrothermal reaction time is 2 to 16 hours.

[0025] Furthermore, in step (1), TiO with a particle size of 5 nm to 20 nm is obtained by alcoholysis. 2 Nanoparticles;

[0026] In step (2), the specific surface area of ​​the obtained catalyst is 50 to 1650 m 2 / g, preferably 1200~1650m 2 The present invention also provides a Sn-doped defective mesoporous TiO prepared according to the preparation method described above. 2 catalyst.

[0027] The present invention also provides the use of the catalyst described above in the preparation of polyglycolic acid. Preferably, the use is the use of the catalyst in the preparation of the polyglycolic acid by direct esterification using glycolic acid as a raw material.

[0028] The technical solution provided by the present invention has the following beneficial effects:

[0029] The catalyst prepared by the preparation method of the present invention has excellent catalytic effect in the reaction of preparing polyglycolic acid by direct esterification and polycondensation of glycolic acid, and can prepare polyglycolic acid with high molecular weight and light color. The prepared catalyst can obtain good catalytic effect with relatively small amount of catalyst, especially when the amount of metal Sn is reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is an electron microscope photograph of the catalyst prepared in Preparation Example 1;

[0031] Figure 2 This is an electron microscope photograph of the catalyst prepared in Preparation Example 5;

[0032] Figure 3 Preparation Example 5 0.05Sn-TiO 2 -4h pore distribution curve;

[0033] Figure 4 EPR curves of the catalysts prepared in Preparation Examples 4 and 5. DETAILED DESCRIPTION

[0034] In order to facilitate the understanding of the present invention, the present invention will be further described below in conjunction with examples. It should be understood that the following examples are only for a better understanding of the present invention and do not mean that the present invention is limited to the following examples.

[0035] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the invention belongs. The term "and / or" as may be used herein includes any and all combinations of one or more of the associated listed items.

[0036] The present invention provides a Sn-doped defective mesoporous TiO 2 The method for preparing the catalyst comprises the following steps:

[0037] (1) alcoholyzing a titanium compound in a polyol, wherein the molar ratio of the titanium compound to the polyol is 0.005 to 0.5, and obtaining TiO 2Then, an alkali solution and an alcohol with a reducing potential are added to carry out a solvent thermal reaction at 120 to 220°C, and the obtained product is washed, separated, and then dried to obtain defective mesoporous TiO 2 ; Wherein, washing is performed by, for example, industrial alcohol, separation is performed by, for example, centrifugal separation, and drying is performed by, for example, vacuum drying;

[0038] (2) The defective mesoporous TiO obtained in step (1) 2 Dispersing in an aqueous solution of a tin compound, performing a hydrothermal reaction at 100-200°C, washing, separating, and then drying the obtained product to obtain the catalyst. The washing is performed, for example, with industrial alcohol, the separation is performed, for example, by centrifugation, and the drying is performed, for example, by vacuum drying;

[0039] The catalyst prepared by the preparation method of the present invention has excellent catalytic effect in the reaction of direct esterification and polycondensation of glycolic acid to prepare polyglycolic acid, and can prepare polyglycolic acid with high molecular weight and light color. 2 The synergistic catalysis can reduce the amount of catalyst, especially the amount of metal Sn, and still achieve good catalytic effect. 2 The high activity of the catalyst is also conducive to reducing the reaction time, thereby reducing energy consumption. The obtained catalyst can inhibit the yellowing of the product and achieve efficient catalytic synthesis of PGA.

[0040] In some embodiments, in step (1), the titanium compound is selected from one or more of tetrabutyl titanate, isopropyl titanate, cesium titanate, potassium titanate, titanyl sulfate, titanium tetrachloride, and titanium trichloride, preferably tetrabutyl titanate and / or titanium tetrachloride, more preferably titanium tetrachloride; using the preferred titanium compound is conducive to obtaining a catalyst with better catalytic performance. Under the condition that other conditions are basically the same, using the preferred titanium compound is conducive to obtaining a higher molecular weight polyglycolic acid while taking into account a relatively low b value.

[0041] In some embodiments, in step (1), the polyol is selected from one or more of propylene glycol, glycerol, ethylene glycol, butylene glycol, and pentanediol, preferably propylene glycol. The use of the preferred polyol is conducive to obtaining a catalyst with better catalytic performance. Under the condition that other conditions are basically the same, the use of propylene glycol is conducive to obtaining polyglycolic acid with a higher molecular weight while still taking into account a relatively low b value.

[0042] In some embodiments, in step (2), the tin compound is selected from one or more of tin dioxide, tin dichloride, tin tetrachloride, stannous oxalate, tin sulfide, and tin nitrate, preferably tin dichloride and / or tin nitrate, more preferably tin dichloride; using the preferred tin compound is conducive to obtaining a catalyst with better catalytic performance.

[0043] In a preferred embodiment, the molar ratio of the titanium compound to the polyol is 0.007-0.2. The preferred molar ratio is advantageous for obtaining a catalyst with better catalytic performance. Under the condition that other conditions are substantially the same, the preferred molar ratio is advantageous for obtaining polyglycolic acid with a higher molecular weight while still taking into account a relatively low b value.

[0044] Furthermore, in step (1), the alkali solution is an aqueous solution of an alkaline compound, and the concentration of the alkali solution is, for example, 5 to 20 wt %; in step (1), the molar ratio of the alkaline compound in the alkali solution to the alcohol having a reducing potential is preferably 0.05 to 0.2; and the molar ratio of the alkaline compound to the titanium compound is preferably 10 to 0.5, for example, 10 to 2.

[0045] In some embodiments, the alkaline compound in the alkali solution is selected from one or more of sodium hydroxide, potassium hydroxide, magnesium hydroxide, aluminum hydroxide, potassium oxide, and potassium carbonate, preferably potassium hydroxide; using the preferred alkaline compound is conducive to obtaining a catalyst with better catalytic performance.

[0046] In some embodiments, the alcohol with reduction potential is selected from one or more of n-butanol, 1,4-butanediol, 1,5-pentanediol, ethylene glycol, propylene glycol, and ethanol, preferably n-butanol. The use of the preferred alcohol with reduction potential is conducive to obtaining a catalyst with better catalytic performance. Under the condition that other conditions are basically the same, the use of the preferred n-butanol is conducive to obtaining a polyglycolic acid with a higher molecular weight, and still taking into account a relatively low b value.

[0047] In a preferred embodiment, the molar ratio of the tin compound used in step (2) to the titanium compound used in step (1) is 0.05 to 0.3;

[0048] In some embodiments, the concentration of the aqueous solution of the tin compound is 0.01 to 0.5 mol / L.

[0049] In some embodiments, in step (1), the alcoholysis temperature is 25 to 200° C., and the alcoholysis time is 0.5 to 12 h;

[0050] In some embodiments, in step (1), the solvent thermal reaction time is 2 to 12 hours;

[0051] In some embodiments, in step (2), the hydrothermal reaction time is 2 to 16 hours.

[0052] The catalyst is prepared by the method of the present invention. In step (1), the molar ratio of the titanium compound to the polyol is controlled to be 0.005 to 0.5. By adjusting the titanium alcohol ratio within this range, the alcoholysis rate can be adjusted, and a monodispersed TiO2 with a particle size between 5 nm and 20 nm can be obtained. 2 Nanoparticles; In step (2), a catalyst with a high specific surface area can be obtained, the specific surface area is, for example, 50 to 1650 m 2 / g, preferably 1200~1650m 2 / g of catalyst.

[0053] The second aspect of the present invention provides a Sn-doped defective mesoporous TiO prepared according to the preparation method described above. 2 catalyst.

[0054] The present invention also provides the use of the catalyst described above in the preparation of polyglycolic acid. Preferably, the catalyst is used in the preparation of the polyglycolic acid by direct esterification using glycolic acid as a raw material.

[0055] The present invention is further described below by way of examples, but it should not be understood that the present invention is limited thereto.

[0056] Where specific experimental steps or conditions are not specified in the examples, the corresponding conventional experimental steps or conditions in the art can be used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be purchased commercially.

[0057] The detection methods involved in the following examples are described as follows:

[0058] b value: Use a colorimeter to perform colorimetric analysis, refer to GB / T 14190-2017 standard. 2 The particle size of nanoparticles was characterized by transmission electron microscopy. The specific surface area of ​​the catalyst was determined by isothermal N 2 Adsorption-desorption test.

[0059] Preparation Example 1

[0060] A Sn-doped defective mesoporous TiO 2 The catalyst was prepared as follows:

[0061] (1) At room temperature, titanium tetrachloride and propylene glycol at a molar ratio of 1:100 were added to a three-necked flask and stirred for 1 h to obtain monodispersed TiO 2Nanoparticles (particle size of 5nm); then add alkali solution and n-butanol (alkali solution is a potassium hydroxide aqueous solution with a mass concentration of 5%, the molar ratio of potassium hydroxide to n-butanol is 0.05, and the molar ratio of potassium hydroxide to titanium tetrachloride used in this step is 10), start heating, heat to 150°C for solvent thermal reaction for 2h, wash the product with industrial alcohol, centrifuge and vacuum dry to obtain defective mesoporous TiO 2 .

[0062] (2) Prepared defective mesoporous TiO 2 The catalyst was dispersed in a 0.05 mol / L tin dichloride aqueous solution (the molar ratio of tin dichloride to titanium tetrachloride used in step (1) was 0.05), and subjected to hydrothermal reaction at 180°C for 2 h. The product was washed with industrial alcohol, centrifuged, and vacuum dried to obtain a catalyst 0.05Sn-TiO 2 -B, specific surface area is 1225m 2 / g, electron microscope photos see Figure 1 .

[0063] Preparation Example 2 (Compared with Example 1, the amount of tin dichloride used in step (2) is different)

[0064] A Sn-doped defective mesoporous TiO 2 The catalyst was prepared as follows:

[0065] (1) At room temperature, titanium tetrachloride and propylene glycol at a molar ratio of 1:100 were added to a three-necked flask and stirred for 1 h to obtain monodispersed TiO 2 Nanoparticles (particle size of 5nm); then add alkali solution and n-butanol (alkali solution is a potassium hydroxide aqueous solution with a mass concentration of 5%, the molar ratio of potassium hydroxide to n-butanol is 0.05, and the molar ratio of potassium hydroxide to titanium tetrachloride used in this step is 10), start heating, heat to 150°C for solvent thermal reaction for 2h, wash the product with industrial alcohol, centrifuge and vacuum dry to obtain defective mesoporous TiO 2 .

[0066] (2) Prepared defective mesoporous TiO 2 The catalyst was dispersed in a 0.1 mol / L tin dichloride aqueous solution (the molar ratio of tin dichloride to titanium tetrachloride used in step (1) was 0.1), and subjected to hydrothermal reaction at 180°C for 2 h. The product was washed with industrial alcohol, centrifuged, and vacuum dried to obtain a catalyst 0.1Sn-TiO 2 -B, with a specific surface area of ​​1220m 2 / g.

[0067] Preparation Example 3 (Compared with Example 1, the polyol in step (1) is changed to ethylene glycol)

[0068] A Sn-doped defective mesoporous TiO 2 The catalyst was prepared as follows:

[0069] (1) At room temperature, titanium tetrachloride and ethylene glycol at a molar ratio of 1:100 were added to a three-necked flask and stirred for 1 h to obtain monodispersed TiO 2 Nanoparticles (particle size is 20nm), then add alkali solution and n-butanol (the alkali solution is a potassium hydroxide aqueous solution with a mass concentration of 5wt%, the molar ratio of potassium hydroxide to n-butanol is 0.05, and the molar ratio of potassium hydroxide to titanium tetrachloride used in this step is 10), start heating, heat to 150°C for solvothermal reaction for 2h, wash the product with industrial alcohol, centrifuge and vacuum dry to obtain defective mesoporous TiO2.

[0070] (2) Prepared defective mesoporous TiO 2 The catalyst was dispersed in a 0.05 mol / L tin dichloride aqueous solution (the molar ratio of tin dichloride to titanium tetrachloride used in step (1) was 0.05), and subjected to hydrothermal reaction at 180°C for 2 h. The product was washed with industrial alcohol, centrifuged, and vacuum dried to obtain a catalyst 0.05Sn-TiO 2 -EG, specific surface area is 1050m 2 / g.

[0071] Preparation Example 4 (Compared with Example 1, the molar ratio of potassium hydroxide to n-butanol in step (1) was changed)

[0072] A Sn-doped defective mesoporous TiO 2 The catalyst was prepared as follows:

[0073] (1) At room temperature, titanium tetrachloride and propylene glycol at a molar ratio of 1:100 were added to a three-necked flask and stirred for 1 h to obtain monodispersed TiO 2 Nanoparticles (particle size of 5nm), then add alkali solution and n-butanol (alkali solution is a potassium hydroxide aqueous solution with a mass concentration of 5%, the molar ratio of potassium hydroxide to n-butanol is 0.1, and the molar ratio of potassium hydroxide to titanium tetrachloride used in this step is 10), start heating, heat to 150℃ for solvent thermal reaction for 2h, wash the product with industrial alcohol, centrifuge and vacuum dry to obtain defective mesoporous TiO 2 .

[0074] (2) Prepared defective mesoporous TiO 2 The catalyst was dispersed in a 0.05 mol / L tin dichloride aqueous solution (the molar ratio of tin dichloride to titanium tetrachloride used in step (1) was 0.05), and subjected to hydrothermal reaction at 180°C for 2 h. The product was washed with industrial alcohol, centrifuged, and vacuum dried to obtain a catalyst 0.05Sn-TiO 2-0.1, specific surface area is 1310m 2 / g, EPR curve see Figure 4 .

[0075] Preparation Example 5 (Compared with Example 1, the hydrothermal reaction time in step (2) was extended from 2 h to 4 h)

[0076] A Sn-doped defective mesoporous TiO 2 The catalyst was prepared as follows:

[0077] (1) At room temperature, titanium tetrachloride and propylene glycol at a molar ratio of 1:100 were added to a three-necked flask and stirred for 1 h to obtain monodispersed TiO 2 Nanoparticles (particle size of 5nm), then add alkali solution and n-butanol (alkali solution is a potassium hydroxide aqueous solution with a mass concentration of 5%, the molar ratio of potassium hydroxide to n-butanol is 0.05, and the molar ratio of potassium hydroxide to titanium tetrachloride used in this step is 10), start heating, heat to 150℃ for solvent thermal reaction for 2h, wash the product with industrial alcohol, centrifuge and vacuum dry to obtain defective mesoporous TiO 2 .

[0078] (2) Prepared defective mesoporous TiO 2 The catalyst was dispersed in a 0.05 mol / L tin dichloride aqueous solution (the molar ratio of tin dichloride to titanium tetrachloride used in step (1) was 0.05), and subjected to hydrothermal reaction at 180°C for 4 h. The product was washed with industrial alcohol, centrifuged, and vacuum dried to obtain a catalyst 0.05Sn-TiO 2 -4h, specific surface area is 1650m 2 / g, electron microscope photos see Figure 2 , pore distribution curve see Figure 3 , EPR curve see Figure 4 From the characterization results, we can see that Sn-doped defective mesoporous TiO 2 catalyst.

[0079] Example 1

[0080] 0.1 mol of glycolic acid was used as the raw material, and 0.05 Sn-TiO 2 -B is a catalyst, the amount of catalyst used (calculated as titanium dioxide) is 0.04 mol% of glycolic acid, the esterification reaction is carried out under nitrogen protection, the esterification is carried out at 190°C for 1.5 hours, and the condensation reaction is stopped at 220°C for 2 hours to obtain the product PGA1. The obtained product is subjected to GPC (gel permeation chromatography) test and color value test. The test results are shown in Table 1.

[0081] Example 2 (Compared with Example 1, the amount of catalyst is increased)

[0082] 0.1 mol of glycolic acid was used as the raw material, and 0.05 Sn-TiO 2 -B is a catalyst, the amount of catalyst used (calculated as titanium dioxide) is 0.08% molar amount of glycolic acid, and the esterification reaction is carried out under nitrogen protection, the esterification is carried out at 190°C for 1.5 hours, and the condensation reaction is stopped at 220°C for 2 hours to obtain the product PGA2. The obtained product is subjected to GPC test and color value test. The test results are shown in Table 1.

[0083] Example 3

[0084] 0.1 mol of glycolic acid was used as the raw material, and 0.1Sn-TiO 2 -B is a catalyst, the amount of catalyst used (calculated as titanium dioxide) is 0.04 mol% of glycolic acid, the esterification reaction is carried out under nitrogen protection, the esterification is carried out at 190°C for 1.5 hours, and the condensation reaction is stopped at 220°C for 2 hours to obtain the product PGA3. The obtained product is subjected to GPC test and color value test. The test results are shown in Table 1.

[0085] Example 4

[0086] 0.1 mol glycolic acid was used as raw material, and 0.05 Sn-TiO 2 -EG was used as the catalyst, and the amount of the catalyst (calculated as titanium dioxide) was 0.04% molar amount of glycolic acid. The esterification reaction was carried out under nitrogen protection, the esterification was carried out at 190°C for 1.5 hours, and the condensation reaction was stopped at 220°C for 2 hours to obtain the product PGA4. The obtained product was subjected to GPC and color value tests. The test results are shown in Table 1.

[0087] Example 5

[0088] 0.1 mol of glycolic acid was used as the raw material, and 0.05 Sn-TiO 2 -0.1 was used as the catalyst, the amount of the catalyst (calculated as titanium dioxide) was 0.04 mol% of glycolic acid, the esterification reaction was carried out under nitrogen protection, the esterification was carried out at 190°C for 1.5 h, and the condensation reaction was stopped at 220°C for 2 h to obtain the product PGA5. The obtained product was subjected to GPC and color value tests. The test results are shown in Table 1.

[0089] Example 6

[0090] 0.1 mol of glycolic acid was used as the raw material, and 0.05 Sn-TiO 2 -4h was used as catalyst, the amount of catalyst used (calculated as titanium dioxide) was 0.04 mol% of glycolic acid, the esterification reaction was carried out under nitrogen protection, the esterification was carried out at 190°C for 1.5h, and the condensation reaction was stopped at 220°C for 2h to obtain the product PGA6. The obtained product was subjected to GPC and color value tests. The test results are shown in Table 1.

[0091] Example 7 (Compared with Example 1)

[0092] The catalyst used in Example 7 was prepared with reference to Preparation Example 1, except that the catalyst used was different. The catalyst used in Example 7 was prepared with reference to Preparation Example 1, and the difference from Preparation Example 1 was that in step (1), the molar ratio of titanium tetrachloride to propylene glycol was 0.005, and the catalyst 0.05Sn-TiO 2 (0.005).

[0093] Using 0.1 mol glycolic acid as raw material, 0.05Sn-TiO 2 (0.005) was used as the catalyst, the amount of the catalyst (calculated as titanium dioxide) was 0.04 mol% of glycolic acid, the esterification reaction was carried out under nitrogen protection, the esterification was carried out at 190°C for 1.5 h, and the condensation reaction was stopped at 220°C for 2 h to obtain the product PGA7. The obtained product was subjected to GPC test and color value test. The test results are shown in Table 1.

[0094] Embodiment 8 (compared with embodiment 1)

[0095] The catalyst used in Example 8 was prepared by referring to Example 1, except that the catalyst used was different. The catalyst used in Example 8 was prepared by referring to Example 1. The difference from Example 1 was that in step (1), the molar ratio of titanium tetrachloride to propylene glycol was 0.5, and the catalyst 0.05Sn-TiO 2 (0.5).

[0096] Using 0.1 mol glycolic acid as raw material, 0.05Sn-TiO 2 (0.5) was used as the catalyst, and the amount of the catalyst (calculated as titanium dioxide) was 0.04% by mole of glycolic acid. The esterification reaction was carried out under nitrogen protection, the esterification was carried out at 190°C for 1.5 hours, and the condensation reaction was stopped at 220°C for 2 hours to obtain the product PGA8. The obtained product was subjected to GPC test and color value test. The test results are shown in Table 1.

[0097] Example 9 (Compared with Example 1, titanium tetrachloride was used instead of isopropyl titanate)

[0098] The catalyst used in Example 9 was prepared with reference to Preparation Example 1, except that the catalyst used was different. The catalyst used in Example 9 was prepared with reference to Preparation Example 1. The difference from Preparation Example 1 was that in step (1), titanium tetrachloride was replaced with isopropyl titanate to obtain a catalyst 0.05Sn-TiO 2 -TT.

[0099] Using 0.1 mol glycolic acid as raw material, 0.05Sn-TiO 2-TT was used as a catalyst, and the amount of the catalyst (calculated as titanium dioxide) was 0.04% molar amount of glycolic acid. The esterification reaction was carried out under nitrogen protection, the esterification was carried out at 190°C for 1.5 hours, and the polycondensation reaction was stopped at 220°C for 2 hours to obtain the product PGA9. The obtained product was subjected to GPC test and color value test. The test results are shown in Table 1.

[0100] Example 10 (Compared with Preparation Example 1, n-butanol was replaced by 1,5-pentanediol)

[0101] The catalyst used in Example 10 was prepared with reference to Preparation Example 1, and the difference from Preparation Example 1 was that in step (1), n-butanol was replaced with 1,5-pentanediol to obtain a catalyst 0.05Sn-TiO 2 -PTD.

[0102] Using 0.1 mol glycolic acid as raw material, 0.05Sn-TiO 2 -PTD was used as a catalyst, and the amount of the catalyst (calculated as titanium dioxide) was 0.04% molar amount of glycolic acid. The esterification reaction was carried out under nitrogen protection, the esterification was carried out at 190°C for 1.5 hours, and the polycondensation reaction was stopped at 220°C for 2 hours to obtain the product PGA10. The obtained product was subjected to GPC test and color value test. The test results are shown in Table 1.

[0103] Example 11 (Compared with Example 1, the solvent thermal reaction temperature was adjusted to 120° C.)

[0104] The catalyst used in Example 11 was prepared in accordance with Example 1, except that the catalyst used was different. The catalyst used in Example 11 was prepared in accordance with Example 1. The difference from Example 1 was that in step (1), the temperature of the solvent thermal reaction was adjusted from 150°C to 120°C to obtain a catalyst 0.05Sn-TiO 2 -120.

[0105] Using 0.1 mol glycolic acid as raw material, 0.05Sn-TiO 2 -120 was used as the catalyst, the amount of the catalyst (calculated as titanium dioxide) was 0.04 mol% of glycolic acid, the esterification reaction was carried out under nitrogen protection, the esterification was carried out at 190°C for 1.5 h, and the condensation reaction was stopped at 220°C for 2 h to obtain the product PGA11. The obtained product was subjected to GPC test and color value test. The test results are shown in Table 1.

[0106] Example 12 (Compared with Example 1, the temperature of the hydrothermal reaction is 100° C.)

[0107] The catalyst used in Example 12 was prepared according to Example 1, except that the catalyst used was different. The catalyst used in Example 12 was prepared according to Example 1, and the difference from Example 1 was that in step (2), the temperature of the hydrothermal reaction was adjusted from 180°C to 100°C to obtain a catalyst 0.05Sn-TiO 2 -100.

[0108] Using 0.1 mol glycolic acid as raw material, 0.05Sn-TiO 2 -100 was used as the catalyst, the amount of the catalyst (calculated as titanium dioxide) was 0.04 mol% of glycolic acid, the esterification reaction was carried out under nitrogen protection, the esterification was carried out at 190°C for 1.5 h, and the condensation reaction was stopped at 220°C for 2 h to obtain the product PGA12. The obtained product was subjected to GPC test and color value test. The test results are shown in Table 1.

[0109] Comparative Example 1 (Compared with Example 1, the catalyst is different)

[0110] Using 0.1 mol of glycolic acid as a raw material and commercial stannous octoate as a catalyst, the catalyst dosage is 0.04% molar amount of glycolic acid, and the esterification reaction is carried out under nitrogen protection. The esterification is carried out at 190° C. for 1.5 h, and the condensation reaction is stopped at 220° C. for 2 h to obtain the product PGAD1. The obtained product is subjected to GPC (gel permeation chromatography) test and color value test. The test results are shown in Table 1.

[0111] Comparative Example 2 (compared with Comparative Example 1, the amount of catalyst was increased)

[0112] Using 0.1 mol of glycolic acid as a raw material and commercial stannous octoate as a catalyst, the catalyst dosage is 0.08% molar amount of glycolic acid, and the esterification reaction is carried out under nitrogen protection. The esterification is carried out at 190°C for 1.5 hours, and the condensation reaction is stopped at 220°C for 2 hours to obtain the product PGAD2. The obtained product is subjected to GPC test and color value test. The test results are shown in Table 1.

[0113] Comparative Example 3 (Compared with Example 1, the catalyst is different)

[0114] Using 0.1 mol of glycolic acid as raw material and commercial titanium dioxide P25 as catalyst, the catalyst dosage is 0.04% molar amount of glycolic acid, and the esterification reaction is carried out under nitrogen protection. The esterification is carried out at 190°C for 1.5 hours, and the condensation reaction is stopped at 220°C for 2 hours to obtain the product PGAD3. The obtained product is subjected to GPC test and color value test. The test results are shown in Table 1.

[0115] Comparative Example 4 (Compared with Comparative Example 4, the amount of catalyst was increased)

[0116] Using 0.1 mol of glycolic acid as a raw material and commercial titanium dioxide P25 as a catalyst, the catalyst dosage is 0.08% molar amount of glycolic acid, and the esterification reaction is carried out under nitrogen protection. The esterification is carried out at 190°C for 1.5 hours, and the condensation reaction is stopped at 220°C for 2 hours to obtain the product PGAD4. The obtained product is subjected to GPC and color value tests. The test results are shown in Table 1.

[0117] Table 1 GPC and b value test results of prepared PGA

[0118]

[0119]

[0120] The results show that the Sn-doped defective mesoporous TiO prepared by the present invention 2 Compared with traditional polyester catalysts, the catalyst has the following advantages:

[0121] 1) Low preparation cost, high catalytic activity and good stability;

[0122] 2) Doping with a small amount of Sn can still achieve good catalytic effect when reducing the amount of catalyst, especially reducing the amount of Sn;

[0123] 3) The catalyst prepared by the preparation method of the present invention can be prepared by adjusting the material ratio, reaction conditions, raw material types, etc. to obtain defective mesoporous TiO 2 The morphology and size can be adjusted, the catalyst activity can be controlled, the lactide content can be effectively reduced and other side reactions can be inhibited, and a higher molecular weight PGA can be prepared. The prepared PGA has high quality, good color and low b value. The catalyst of the present invention is beneficial to improving the reaction efficiency of preparing polyglycolic acid (PGA) by direct esterification, shortening the reaction time, reducing energy consumption, and having the effect of inhibiting yellowing of the product.

[0124] It is easy to understand that the above embodiments are only examples for clear explanation and do not mean that the present invention is limited thereto. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the present invention.

Claims

1. A Sn-doped defective mesoporous TiO 2 A method for preparing a catalyst, It is characterized in that The steps include: (1) alcoholyzing a titanium compound in a polyol, wherein the molar ratio of the titanium compound to the polyol is 0.005 to 0.5, and obtaining TiO 2 Then, an alkali solution and an alcohol with a reducing potential are added to carry out a solvent thermal reaction at 120 to 220°C, and the obtained product is washed, separated, and then dried to obtain defective mesoporous TiO 2 ; (2) The defective mesoporous TiO obtained in step (1) 2 The catalyst is obtained by dispersing the catalyst in a tin compound aqueous solution and performing a hydrothermal reaction at 100-200°C. The obtained product is washed, separated and then dried.

2. The preparation method according to claim 1, It is characterized in that In step (1), the titanium compound is selected from one or more of tetrabutyl titanate, isopropyl titanate, cesium titanate, potassium titanate, titanyl sulfate, titanium tetrachloride, and titanium trichloride, preferably tetrabutyl titanate and / or titanium tetrachloride, more preferably titanium tetrachloride; And / or, in step (1), the polyol is selected from one or more of propylene glycol, glycerol, ethylene glycol, butylene glycol, and pentanediol, preferably propylene glycol; And / or, in step (2), the tin compound is selected from one or more of tin dioxide, tin dichloride, tin tetrachloride, stannous oxalate, tin sulfide, and tin nitrate, preferably tin dichloride and / or tin nitrate, more preferably tin dichloride.

3. The preparation method according to claim 1 or 2, It is characterized in that The molar ratio of the titanium compound to the polyol is 0.007-0.

2.

4. The preparation method according to any one of claims 1 to 3, It is characterized in that In step (1), the alkali solution is an aqueous solution of an alkaline compound; In step (1), the molar ratio of the alkaline compound in the alkali solution to the alcohol having a reducing potential is 0.05 to 0.2; and the molar ratio of the alkaline compound to the titanium compound is 10 to 0.

5.

5. The preparation method according to any one of claims 1 to 4, It is characterized in that The alkaline compound in the alkali solution is selected from one or more of sodium hydroxide, potassium hydroxide, magnesium hydroxide, aluminum hydroxide, potassium oxide, and potassium carbonate, preferably potassium hydroxide; And / or, the alcohol having a reducing potential is selected from one or more of n-butanol, 1,4-butanediol, 1,5-pentanediol, ethylene glycol, propylene glycol, and ethanol, preferably n-butanol.

6. The preparation method according to any one of claims 1 to 5, It is characterized in that The molar ratio of the tin compound used in step (2) to the titanium compound used in step (1) is 0.05 to 0.3; Preferably, the concentration of the tin compound aqueous solution is 0.01-0.5 mol / L.

7. The preparation method according to any one of claims 1 to 6, It is characterized in that In step (1), the alcoholysis temperature is 25 to 200° C., and the alcoholysis time is 0.5 to 12 h; And / or, in step (1), the solvent thermal reaction time is 2 to 12 hours; And / or, in step (2), the hydrothermal reaction time is 2 to 16 hours.

8. The preparation method according to any one of claims 1 to 7, It is characterized in that In step (1), TiO with a particle size of 5 nm to 20 nm is obtained by alcoholysis. 2 Nanoparticles; In step (2), the specific surface area of ​​the obtained catalyst is 50 to 1650 m 2 / g, preferably 1200~1650m 2 / g.

9. A Sn-doped defective mesoporous TiO prepared by the preparation method according to any one of claims 1 to 8 2 catalyst.

10. Use of the catalyst according to claim 9 in the preparation of polyglycolic acid, preferably, the use is the use of the catalyst in the preparation of the polyglycolic acid by direct esterification using glycolic acid as a raw material.